Correlates and trends of 'ogogoro' alcohol herbs use among traders of Lagos mile two (2007)
"The study examined some correlates and trends of 'Ogogoro herbs' use among 376 traders in the mile two market Lagos' and environs who responded to the study's questionnaires. Their mean (x) age was 29.25 years and standard deviation (SD) of 2.06 with age range of 20 - 41 years. Three research problems were resolved with the Pearson product moment correlation (r) and T test for the data analysis. The results revealed that there was significant correlation between the knowledge and belief about Ogogoro local herbs use (r = 57, P < .05) and knowledge and use of Ogogoro local herbs (r = 23, P. <. 05) and between belief and the Ogogoro local herbs use (r = 55, P. < .05). Also, the result revealed that drivers and riders were heavily use of Ogogoro local herbs than sellers and buyers (t = 2, 367 = 4,533; P < .05). While male traders used Ogogoro herbs than female counter parts (Male, x = 5.83 and Female, Mean x = 3.99 with t = 2.367 = 9, 82 P. < .05). It was concluded that majority of the marketers engaged in heavy Ogogoro local herb consumption. Major consequences were highlighted with some suggestions and recommendations for the relevant stakeholders in formulating appropriate policy on the preventive programmes in Nigeria."